Palliative stent implantation for coarctation in neonates and young infants - Isabel Sreeram; Narayanswami Sreeram; Gerardus Bennink (Wolters Kluwer Medknow Publications, 2012)
Background: In selected neonates and infants, primary palliative stent implantation may be indicated for coarctation of the aorta. We describe our experience with this approach in five consecutive patients. Methods: Five neonates and infants (age range 6 to 68 days, gestation 33 to 38 weeks, weight range at procedure of between 1650 to 4000 g) underwent palliative stent implantation as primary therapy for coarctation of the aorta. Indications for primary stent implantation were varied. All procedures were performed by elective surgical cut down of the axillary artery. Standard coronary stents (diameter 4.5 to 5 mm, length 12 to 16 mm) were delivered via a 4F sheath. The axillary artery was repaired after removal of the sheath. Results: All procedures were acutely successful, and without procedural complications. All patients survived to hospital discharge. Four patients have subsequently undergone elective stent removal and surgical repair of the arch, at between 38 and 83 days following stent implantation. Complete stent removal was achieved in three patients. Over a follow-up ranging between 8 weeks and 36 months, none of the patients has had any further complications. Conclusions: This palliative approach is warranted in carefully selected patients. Long-term follow-up is required.